Genetska identifikacija pogrešanih oseb - Bajželj, Matija (Zdravniški vestnik, 2017)
This article presents identification of missing persons from badly preserved post-mortem remains using molecular genetics methods. Extremely polymorphic and individually specific genetic markers that enable the identification of missing persons are microsatellites on autosomal chromosomes, microsatellites on Y chromosome and control region of mitochondrial DNA. For genetic profile comparison, biological material from post-mortem remains and reference samples have to be collected. If post-mortem remains are found shortly after the presumed death of the missing person, their personal items are used for comparison. If these are not available, (the missing person%s) relatives could be used as reference samples or achieved tissues stored in medical institutions if biopsy for the needs of medical diagnostics was performed earlier during their life. When reference samples are not available, genetic identification is not possible. The type of biological material sampled from the deceased depends on the condition of human remains. Blood, soft tissues, nails, teeth or bones are most commonly used for genetic identification, and the time required for DNA extraction depends on the type of biological material. The most demanding and time consuming is extraction of DNA from teeth and bones, therefore we use it in cases when only skeleton is available or we cannot get a sufficient amount of DNA for genetic identification from other tissues. If the genetic profile of post-mortem reamains and a reference sample of the missing person match, the strength of genetic evidence has to be statistically evaluated and the probability of identification reported.
Keywords: človeški posmrtni ostanki; genetic typing; genetska tipizacija; human remains; identification; identifikacija